AB1402-HPR CHILDRENS COMFORT COUNTS – CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITISEXPERIENCE OF USING ENTONOX AS AN ANALGESIC AGENT FOR INTRA-ARTICULAR JOINT INJECTIONS. (June 2019) - O'Keeffe, Norma; Lowry, Clodagh; Lambert, Veronica; Muldoon, Maeve
Abstract : Background: Intra-articular corticosteroid injections (IACI) are frequently used in the medical management for children with juvenile idiopathic arthritis (JIA) as they allow treatment to be administered directly into a specific inflamed joint which may negate the requirement for further systemic medication or provide an adjuvant to them (1). However IACIs are often associated with significant pain and discomfort for children. Inhaled Entonox gas (50% nitrous oxide and 50% oxygen) is widely used as an analgesic and anxiolytic agent to reduce pain and anxiety for a variety of painful procedural in children. Evidence from a variety of different procedures has shown it to be an effective, safe and patient acceptable form of analgesia for both adults and children (2). It is widely acknowledged that patient satisfaction questionnaires allow clinicians to acquire meaningful and essential information that identifies gaps in care and facilitates the development of effective action plans for quality improvement in healthcare (3). Objectives: The objective of this study was to assess children with JIA level of satisfaction and acceptability of using inhaled Entonox for IACI in a pediatric day-care unit. Methods: Between the years 2017 and 2018, Entonox gas was administered to 48 children with JIA for Intra-articular corticosteroid injections in Temple Street Childrens University Hospital. Following this procedure children were invited to complete a modified version of a previously validated questionnaire (4). Results: Of the 48 children approached, 32 completed the questionnaire (response rate =66.6%). The respondents ranged in age from 7-17 years and for 22 (69%) of the children it was their first time having an IACI. While 25% of respondents reported being nervous or scared before the procedure, 100% of the children who completed the questionnaire reported that if they required another IACI in the future they would like to use Entonox again. Conclusion: Overall satisfaction was high with all children reporting that they would be willing to use Entonox again if required. Furthermore satisfaction with the care provided by the clinicians was also rated very highly. References: [1] Casado R, Lumbreras J, De Inocencio J, Remesal A, Merino R. Garcia-Cconsueqra. Sedation for intra-articular corticosteroid injections in juvenile idiopathic arthritis: the views of patients and their parents. Eur J Pediatrics. 2013; 172:14113. [2] Young A, Ismail M, Papatsoris AG, Barua JM, Calleary JG, Masood J. Entonox inhalation to reduce pain in common diagnostic and therapeutic outpatient urological procedures: a review of the evidence. Ann R Coll Surg Engl. 2012; 94(1):81. [3] Al-Abri R, Al-Balushi A. Patient satisfaction survey as a tool towards quality improvement. Oman Med J. 2014; 29(1):37. [4] Lew, VK, Lalwani, K, Palermo, TM Factors affecting parental satisfaction following pediatric procedural sedation. J Clin Anesth. (2010). 22 2934. Acknowledgement: We wish to thanks all our colleagues in Temple Street Children's University Hospital and Dublin City University for their support and assistance in completing this project. Disclosure of Interests: Norma O'Keeffe Consultant for: Norvatis, Speakers bureau: Abbvie, Clodagh Lowry: None declared, veronica lambert: None declared, Maeve Muldoon: None declared